1987
DOI: 10.1111/j.1464-410x.1987.tb04953.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral Ciprofloxacin as Prophylaxis in Transurethral Resection of the Prostate

Abstract: A new quinolone antibacterial, ciprofloxacin, was evaluated as oral prophylaxis for transurethral resection of the prostate in a randomised controlled trial. A 3-day course of perioperative ciprofloxacin 250 mg twice daily reduced the post-operative infection rate, the post-operative hospital stay and the frequency of infective complications. Ciprofloxacin was well tolerated and no significant haematological or biochemical side effects were detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Postoperative UTIs and bacteremia were the typical complications of TUR‐P, so effective AMP is necessary. Many studies on the necessity of AMP for TUR‐P have been reported 3,13,14,46–89 . Among them, many randomized comparative studies and meta‐analysis 88,89 were included.…”
Section: Detailed Expositionmentioning
confidence: 99%
“…Postoperative UTIs and bacteremia were the typical complications of TUR‐P, so effective AMP is necessary. Many studies on the necessity of AMP for TUR‐P have been reported 3,13,14,46–89 . Among them, many randomized comparative studies and meta‐analysis 88,89 were included.…”
Section: Detailed Expositionmentioning
confidence: 99%
“…Fluoroquinolones (FQs) are widely prescribed antibiotics (reportedly becoming the most common class of antibiotics prescribed to adults in 2002)1 used to treat pneumonia,2–4 sinusitis,2–4 bronchitis2–4 and urinary tract infections,2 5 and also employed for prostate procedure prophylaxis,6 7 among other indications 8–11. As with all drugs, FQs have the potential for adverse effects (AEs) 8–15…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Murdoch et al (29), although preoperative bacteriuria was an exclusion criterion, 14 patients with significant preoperative bacteriuria were included in the trial. In the study of Hellsten et al (30) patients were not stratified according to urine culture status preoperatively, and the study of Ueda et al (Table 2) did not specify whether the preoperative urine was infected or not.…”
Section: Some Of the Pathogens Responsible For Infection Following Inmentioning
confidence: 99%